(3NdGUI GdMSGHs - (3GdMGQKj GdYGedj GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s
(3ChdgG (B:s
(3fMeOc (B..(3hQJHJgG Ydi ebOeI hYTQI CHhGH (B, (3GdMSGH Yde jSJYde efg cjajI GSJNQGL GdeLghdGJ GdYOOjI ef eYdheGJ eNUhUI hehVhYg GdYOO GdMGUd aj GdeGOI ceG bjd hef Ke YO GdMSGH ef GdQjGVI (B...s
(3BNQgG (B:s
... (3hdG JHOdgG GdcKja GdWHY ef GdWdGH dFdG jchf eYdbG cGdOQ aj GYfGb GdcdGH aEf cKjQG ef eWGdHgG MQj HGdUjGfI hGdcJeGf Mbjb HGdGSJJGQ Yf (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B6\ 102s
(3GdPQjYI (B7\1078s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdQjGVjGJs